Meningkatkan Motivasi dan Hasil Belajar Matematika dengan Metode Kooperatif Tipe Jigsaw di SMA Negeri 1 Gerung - Raden Roro Sri Heryekti Pujingsih (Jurnal Paedagogy, 2021)
This study aims to improve motivation and mathematics learning outcomes through the application of the jigsaw cooperative learning model for class X-4 students at SMA Negeri 1 Gerung. This research method uses classroom action research. The research subjects were students of class X-4 with a total of 36 students. The research procedure was carried out on a cycle basis. Each cycle consists of planning activities, implementing actions, observing, and reflecting activities. The instruments used to collect research data consisted of tests and observation sheets. The research data were analyzed descriptively by using a percentage to see the trends that occurred in learning activities. The results showed that; (1) the application of the jigsaw cooperative learning model can increase student motivation in the teaching and learning process, (2) student motivation shows that in cycle 1 is 75% and an increase in cycle 2 becomes 84.7%; and (3) students' mastery of the learning material also showed satisfactory results, in cycle 1 students achieved 77.8% completeness, while in cycle 2 students achieved 88.9% completeness.